HIỆN TRẠNG CHẤT LƯỢNG RONG CÂU NGUYÊN LIỆU TẠI MỘT SỐ TỈNH VEN BIỂN PHÍA BẮC - Đỗ, Anh Duy; Lê, Anh Tùng; Bùi, Thị Hiền (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
CURRENT STATUS OF Gracilaria SEAWEED QUALITIES OF SOME NORTHERN COASTAL PROVINCES IN VIET NAMGracilaria seaweed is the main raw material for the extraction of agar, a widely used polysaccharide in the food industry. The results analysis of raw seaweed samples collected from the May to the June 2021 survey in 11 northern coastal provinces showed that the level of impurities in raw seaweed was quite high, reached 24.8 ± 5.2% dry weight. Agar content in raw seaweed averaged 18.7 ± 2.3% dry weight; agar freezing capacity 243.7 ± 29.6 g/cm2; agar freezing temperature 34.5 ± 0.3oC. The protein content of dry seaweed ranges from 9.38% to 12.75%, lipid - from 1.06% to 1.28%, and inorganic salts - from 20.85% to 22.17%. The results of this analysis also showed that the content and quality of raw seaweed has significantly decreased compared to the past. Therefore, it is necessary to develop solutions to improve the quality of raw seaweed sources in our country in the future to satisfy the needs of domestic production and export.